Reynoutria japonica, an invasive herb as a source of activated carbon for the removal of xenobiotics from water - Koutník, Ivan; Vráblová, Martina; Bednárek, Jan (Bioresource technology, 2020)
Japanese knotweed (JK) is considered one of the most problematic invasive plants. Great attention was paid to research any possibilities of reducing its occurrence. This work deals with possibilities of easy transformation of JK into carbon adsorbent (AC), which is usable for sorption of diclofenac and paracetamol. Activated carbons were prepared by microwave heating using H3PO4, NaOH and sodium methanolate as the chemical agents. Characterization of AC's was carried out using BET, ATR-FTIR, SEM, adsorption equilibrium and kinetics experiments. The pseudo-second-order model showed the best similarity criteria for all studied systems adsorbent/adsorbate. The sorption efficiency was influenced by the choice of activating agent, where the π-π interactions between the planes of the obtained adsorbent and the aromatic rings of adsorbate and the interactions between the adsorbate and AC functional groups of the surface played an important role. AC-H3PO4 exhibited highest adsorption capacity for both diclofenac (87.09 mg.g-1) and paracetamol (136.61 mg.g-1).
Keywords: Japanese knotweed; kinetika; Adsorption; koncentrace vodíkových iontů; adsorpce; Charcoal; Water Pollutants, Chemical; Kinetics; Xenobiotics; Hydrogen-Ion Concentration; Water; Active carbon; dřevěné a živočišné uhlí; xenobiotika; Microwave activation; chemické látky znečišťující vodu; voda